Fuzzy goal programming technique for solving flexible assignment problem in PCB assembly line - Hu, Kuo-Jen (Journal of information & optimization sciences, 2017)
In this paper, we construct the multiple objectives programming for the PCB line assignment problem based on the Assignment Problem (AP) and Transportation Problem (TP) models, which employs the fuzzy goal programming technique with nonlinear membership function for solving this multiple objectives programming problem. This computational mathematics has been addressed to solve an AP under uncertainty and in real world scenarios is using fuzzy theory. Fuzzy goal programming technique usually deals with flexible aspiration levels that are indicative of optimality when considering all objectives or goals simultaneously with possible deviation in objectives or constraints in vague, imprecise and uncertain environment. Therefore; the proposed model will give a compromise solution for suitable optimality and adjust the interval objective values of the upper and lower bounds of each objective function for parameters being considered in uncertain environment. Finally, a case study is taken to illustrate the solution procedure.